Perlindungan Hak Tenaga Kerja Penyandang Disabilitas Dalam Mendapatkan Pekerjaan Di Kota Padang - Siregar, Ridwan Efendi; Khairani, Khairani; Fatimah, Titin (Lareh Law Review, 2024)
In general, this study aims to determine the protection of the rights of workers with disabilities in obtaining employment opportunities in the city of Padang and to find out the obstacles in obtaining employment opportunities in the city of Padang and their solutions. The formulation of the problem in this research is, first, how is the protection of the rights of workers with disabilities in getting work opportunities in the city of Padang? Second, what are the obstacles in protecting the rights of workers with disabilities in getting work opportunities in the city of Padang and efforts to solve them? This study uses empirical juridical research methods. The research results obtained were, firstly, protection of the rights of workers with disabilities in obtaining employment opportunities in the city of Padang, in this case, the Government through the Padang City Department of Labor and Industry formed a Disability Service Unit (ULD), condsucted outreach, appealed, provided training and debriefing of workers with disabilities and provide workplaces for persons with disabilities who choose to work in the informal sector. Second, there are obstacles in protecting the rights of workers with disabilities in getting work opportunities in the city of Padang, including the government being unable to intervene in companies, there are no sanctions for companies that do not implement these rules, and there is no clear valid data regarding the number of workers with disabilities. . The solutions that can be given are persuasively appealing to companies to employ people with disabilities, opening training, job training, the government must give appreciation or appreciation to companies that have employed people with disabilities. The conclusion in this study is that the protection of the rights of workers with disabilities in obtaining work opportunities in the city of Padang has not been implemented properly. Keywords : protection of rights, labor, persons with disabilities